Pemahaman Aturan Pajak, Kesadaran Wajib Pajak, Kualitas Pelayanan Pajak Dan Kepatuhan Pelaku E-Commerce di Karesidenan Surakarta - Safitri Nur Rohmah; Erna Chotidjah; Antin Okfitasari (ITB AAS Indonesia Surakarta, 2024)
The aim of this study is to empirically show the effect of understanding tax rules, awareness of taxpayers and quality of tax services on e-commerce compliance. Online trading is inseparable from a tax known as the e-commerce tax. This research method uses a descriptive approach, by collecting data from questionnaires and literature. The data used are primary data by using a Likert scale questionnaire on e-commerce actors in Karasidenan Surakarta. The results of the study prove that understanding of tax rules affects compliance with e-commerce actors, taxpayer awareness does not affect compliance with e-commerce actors and the quality of tax services affects compliance with e-commerce actors.